The Elephant in the Room: Sudden Unexplained Death in Epilepsy Patients - Pınar BEKDİK ŞİRİNOCAK; Ayşe Deniz ELMALI; Betül BAYKAN (Archives of Epilepsy, 2019)
Epilepsy is a disease characterized by recurring seizures. Sudden unexpected death in epilepsy patients (SUDEP), however rare, is very important. Precautions taken against this devastating and irreversible complication have substantial value. This review is a discussion of the definition of SUDEP, possible risk factors, and preventative measures. All neurologists and family medicine practitioners participating in the care of epilepsy patients should be well informed and very aware of this risk and preventative measures, as well as epilepsy patients and their caregivers. More research and programs to raise awareness of SUDEP, a deadly complication of epilepsy, are urgently needed.